Effect of safrole oxide on vascular endothelial cell growth and apoptosis induced by deprivation of fibroblast growth factor. - MIAO Jun-Ying; ZHAO Bao-Xiang; LI Hui-Hui; ZHANG Shang-Li; DU Chun-Qing (Acta Pharmacologica Sinica, 2016)
AIM: To investigate effect of safrole oxide on cell growth and apoptosis induced by deprivation of survival factors (fibroblast growth factors, aFGF and bFGF) in vascular endothelial cells (VEC). METHODS: Morphological changes were observed by light microscopy. Cell growth was determined by MTT (3-[4, 5-dimethylthiazol-2-yl]-2, 5-diphenyltetrazolium) method. DNA fragmentation was analyzed by agarose gel electrophoresis and fluorescence microscopy. Cell cycle distribution was analyzed by flow cytometry (FCM). RESULTS: The cells deprived of FGF were exposed to safrole oxide 5-25 mg/L for 24 h. Cells spreading and growth were promoted (P